(untitled) (Dhaka Shishu (Children) Hospital Journal, 2025)
Background: Pediatric anesthesia for cardiac surgery presents unique challenges, requiring effective pre-anesthetic medications to manage preoperative anxiety and sedation. Objective: This study aims to compare the effectiveness and safety of oral midazolam and oral ketamine as pre-anesthetic medications in pediatric cardiac patients at Bangladesh Shishu Hospital & Institute. Methods: This prospective randomized double-blind clinical trial included 50 pediatric patients scheduled for elective cardiac surgery, randomly assigned to receive either oral midazolam (0.5 mg/kg) or oral ketamine (5 mg/kg) 30 minutes before anesthesia induction. Sedation levels were assessed using the Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) scale. Secondary outcomes included ease of parental separation, mask acceptance, and the occurrence of adverse effects evaluated by a blinded observer. Data were analyzed using SPSS version 26. Results: The mean age of patients was 7.5 years (SD 2.4), with no significant differences between the groups in demographic or clinical characteristics. Deep sedation (score 1) was achieved by 8% of the midazolam group and 4% of the ketamine group (p=0.34). Excellent mask acceptance was observed in 64% of the midazolam group and 56% of the ketamine group (p=0.55). Nausea occurred in 4% of the midazolam group and 12% of the ketamine group (p=0.29), with no significant differences in other adverse effects. Conclusion: Both oral midazolam and oral ketamine are effective and safe for preanesthetic medication in pediatric cardiac patients, with no significant differences in sedation levels, parental separation, mask acceptance, or adverse effects. These findings support the use of both medications in clinical practice, allowing for flexible patient management based on individual needs. DS (Child) H J 2023; 39(2): 83-87